Optimisation and comparison of a phenotypic maldi-tof assay with molecular and phenotypic methods for the rapid identification of selected fungal, nocardia and nontuberculous mycobacteria. - Immelman, Wilma (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020.